Rational bridge maintenance decisions in urban areas - ICASP14; Honfi, Daniel (My University, 2023)
Bridge owners need to make decisions about their assets at various stages in the bridgeﾒs life cycle. Decisions at various project stages are based on different levels of information and various degrees of decision model complexity. In an urban context the consequences of the bridge maintenance interventions often involve large uncertainties due to infrastructure interdependencies, lack of space, parallel development projects, boundaries of ownership and responsibility etc. Furthermore, decisions about bridge reinvestments might need to be made at different organisational levels based on the expected costs of project and might involve various budgets. Prioritization of assets is primarily based on their structural condition and expected costs of intervention. However, for urban bridges often other aspects need to be involved in the decisions analysis, such as accessibility, usability, aesthetics, cultural value etc. Thus, these other relevant characteristics need to be quantified to carry out a formal Bayesian decision analysis. The paper discusses how the specific characteristics of urban bridges influence rational decision-making about their maintenance. In a municipal decision-making context, the optimal decision might differ in different project phases, in light of new information regarding structural condition and intervention costs, changes in budgetary constraints or status of other projects. Practical examples are presented, where Bayesian decision analysis is carried out to make a more informed maintenance-related decision.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED